IMPLIMENTASI MODEL(ASSURE) UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR PKn SISWA KELAS IV SD NEGERI 3 BUDI LESTARI KECAMATAN TANJUNG BINTANG TAHUN AJARAN 2015/2016 - Ponidi, Ponidi; Puastuti, Dwi; Kristina, Marilin (STIT Pringsewu, 2016)
Based on the finding research, the implementation of ASSURE teaching model improves the active learning and achievement in civics of the student of class IV OF SD Negeri 3 Tanjung Bintang Element School. The increase of Students’ active learning can be seen from pre- research. It show that 50% Students are activite. In cycle 1, there are 67% students who are active. It increaces to 80% in cycle 2. The civics achievements of the students of class IV OF SD Negeri 3 Budi Lestari Tanjung Bintang Elementary School in the academik years of 2015/2016 is increased. The increase of students achievement can be seen in the pre research from teaching evaluation. It shows that the achievement of 12% of 25 students is increased. The increase in cycle 1 is 44& while 88% is in cycle 2.